Dietary Phytoestrogens and Their Metabolites as Epigenetic Modulators with Impact on Human Health - Victor Stefan Ionescu; Alexandra Popa; Andrei Alexandru; Emilia Manole; Mihaela Neagu; Sevinci Pop (Antioxidants, 2021)
The impact of dietary phytoestrogens on human health has been a topic of continuous debate since their discovery. Nowadays, based on their presumptive beneficial effects, the amount of phytoestrogens consumed in the daily diet has increased considerably worldwide. Thus, there is a growing need for scientific data regarding their mode of action in the human body. Recently, new insights of phytoestrogens’ bioavailability and metabolism have demonstrated an inter-and intra-population heterogeneity of final metabolites’ production. In addition, the phytoestrogens may have the ability to modulate epigenetic mechanisms that control gene expression. This review highlights the complexity and particularity of the metabolism of each class of phytoestrogens, pointing out the diversity of their bioactive gut metabolites. Futhermore, it presents emerging scientific data which suggest that, among well-known genistein and resveratrol, other phytoestrogens and their gut metabolites can act as epigenetic modulators with a possible impact on human health. The interconnection of dietary phytoestrogens’ consumption with gut microbiota composition, epigenome and related preventive mechanisms is discussed. The current challenges and future perspectives in designing relevant research directions to explore the potential health benefits of dietary phytoestrogens are also explored.